Meningkatkan Kinerja Keuangan dan Nilai Perusahaan Dalam Berinvestasi - Yudhistira Ardana (JURNAL ILMIAH MANAJEMEN & BISNIS, 2018)
This study aims to determine the effect of financial performance on firm value. Data collection was carried out from 2012 until 2017. This study analyzed the effect of financial performance which is proxied by 3 (three) independent variables, namely quick ratio, Return on Assets (ROA), Debt to Total Assets Ratio to Price Book Value (PBV) for companies listed in the Jakarta Islamic Index (JII). The data analysis technique used in this study is using panel data regression. The results of this study are independent variables profitability and solvency ratios have a positive and significant effect on the dependent variable in the form of firm value as measured by Price to Book Value (PBV). While the independent variable liquidity ratio measured by the quick ratio has no influence on the value of the company